Debate: the Malaysian Madani narrative in reviving the tiger economy - Zakaria, Zamzulaila; Zakaria, Zarina; Ferry, Laurence (Routledge, 2025)
The purpose of this debate article is to consider a new approach to governing that appeals to the logic of economic inclusivity, rather than exclusivity, among a multi- racial society as a means of economic revival. We do this through the case of Malaysia.